Growth, Distribution and Politics - Tabellini, Guido Enrico (International Monetary Fund, 1991)
We start by arguing that to understand growth differences across countries and time, one needs to understand differences in public policies that affect the incentives for productive accumulation of capital, human capital, or technically useful knowledge. And to understand policy differences one needs to understand how political institutions aggregate conflicting interests into public policies. We then survey some recent work along these lines, which argues that more inequality leads to slower growth. Next, we illustrate some of the basic ideas of this work, by help of a simple model of taxation. We also present some econometric cross-country evidence, which is largely supportive of the basic ideas. We end by suggestions for further work